Mycoflora assessment, growth and toxigenic features of patulin‐producers in kiwifruit in China. (28th November 2017) - Wang, Yuan; Feng, Kewei; Liu, Bin; Zhang, Zhiwei; Wei, Jianping; Yuan, Yahong; Yue, Tianli
Abstract: BACKGROUND: Fungal development in agricultural products may cause mycotoxin contamination, which is a significant threat to food safety. Patulin (PAT) and PAT‐producer contamination has been established as a worldwide problem. The present study aimed to investigate the mycoflora and PAT‐producers present in kiwifruits and environmental samples collected from orchards and processing plants in Shaanxi Province, China. RESULTS: Variations in mycoflora were observed in different samples, with penicillia and aspergilli as the predominant genera. Approximately 42.86% of dropped fruits were contaminated with PAT‐producers, which harbored the 6‐methylsalicylic acid synthase and the isoepoxydon dehydrogenase genes that are involved in PAT biosynthesis. The growth of Penicillium expansum, Penicillium griseofulvum and Penicillium paneum in kiwi puree agar (KPA) medium and kiwi juice well fitted the modified Gompertz and Baranyi and Roberts models ( R 2 ≥ 0.95). A significant positive correlation between colony diameter and PAT content in KPA medium of P. expansum and P. griseofulvum was observed ( P  < 0.05). CONCLUSIONS: The present study analyzed the mycofloral composition and the potential risk for PAT and PAT‐producer contamination in kiwifruit, which may be utilized in the establishment of proper management practices in the kiwifruit industry. © 2017 Society of Chemical Industry